Complete resection of pure anterior foramen magnum meningioma without neurovascular injuries poses a big challenge: Case report. (April 2021) - Hammed, Ali; Mahfoud, Moufid; Sulaiman, Alaa; Najm, Adnan; Hammed, Salah
Abstract: Introduction and importance: Meningiomas are common neoplasms representing 14.3–19% of all intracranial tumors. Among all the meningiomas, only 1.8–3.2% arises at the foramen magnum (FM) level. Most of the lesions (68%–98%) arising anterolaterally, followed by postolateral, purely posterior and, more rarely, purely anterior. Case presentation: We report a case of A 42-year-old female presented with a history of neck pain with progressive spastic hemiparesis. Clinical Discussion: MRI revealed well-defied pure anterior and on both sides of vertebral artery, foramen magnum lesion. Through conservative transcondylar approach, Lesion was removed totally in a piecemeal fashion. Histopathology revealed meningothelial meningioma. The patient had a dramatic recovery. Conclusion: The exposure allowed by the far-lateral retrocondylar or partial transcondylar approach is adequate for resecting even anterior intradural FMMs. Reports about Foramen magnum meningioma aren't common, but reports on pure anterior foramen magnum meningioma are very rare. The prerequisite for treating FM meningiomas (FMMs) is the perfect knowledge of the surgical anatomy. The opportunity to give the patient a symptom-free and normal life should not be missed in such cases. Highlights: Only 1.8–3.2% of all meningiomas are located at foramen magnum (FM). Foramen magnum meningiomas (FMMs) represent a common histological tumor in a rare and eloquent location. FMMs are one of the most surgically complex conditions in neuro-oncologic surgery. The transcondylar approach is a more advanced technique and the total removal of ventral lesion could be achieved.